2011
DOI: 10.1017/s0963548311000186
|View full text |Cite
|
Sign up to set email alerts
|

Random Graphs with Few Disjoint Cycles

Abstract: The classical Erdős-Pósa theorem states that for each positive integer k there is an f(k) such that, in each graph G which does not have k + 1 disjoint cycles, there is a blocker of size at most f(k); that is, a set B of at most f(k) vertices such that G − B has no cycles. We show that, amongst all such graphs on vertex set {1, . . . , n}, all but an exponentially small proportion have a blocker of size k. We also give further properties of a random graph sampled uniformly from this class, concerning uniquenes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(16 citation statements)
references
References 11 publications
0
16
0
Order By: Relevance
“…Besides those discussed above, examples show that it can be constant (forbidding a star) and it can be linear (forbidding two disjoint triangles). The last statement follows from [10], where it is shown that the class Ex(C 3 ∪ C 3 ) is asymptotically the same as the class of graphs G having a vertex v such that G − v is a forest.…”
Section: Upper Boundsmentioning
confidence: 88%
“…Besides those discussed above, examples show that it can be constant (forbidding a star) and it can be linear (forbidding two disjoint triangles). The last statement follows from [10], where it is shown that the class Ex(C 3 ∪ C 3 ) is asymptotically the same as the class of graphs G having a vertex v such that G − v is a forest.…”
Section: Upper Boundsmentioning
confidence: 88%
“…For two sequences of reals (an) and (bn) which are positive for n sufficiently large, we write anbn if limnanbn=1. The next result extends Theorem 1.2 of on forests. Theorem Let scriptA be a proper addable minor‐closed class of graphs, with growth constant γ ; and let k be a fixed positive integer.…”
Section: Introductionmentioning
confidence: 62%
“…The inclusion (1) is ‘nearly an equality’. To be more precise, it was shown in that as n |(Ex (k+1)C)n|=(1+eΩ(n))|(apexk)n|. Thus Ex (k+1)C consists of apexk together with an exponentially smaller class of ‘exceptional’ graphs. A similar result holds for unlabelled graphs ; we consider only labelled graphs in this paper.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations